Coronary Vasomotor Response to Intracoronary Acetylcholine Injection, Clinical Features, and Long‐term Prognosis in 873 Consecutive Patients With Coronary Spasm: Analysis of a Single‐Center Study Over 20 Years. Issue 4 (15th July 2013) - Sato, Koji; Kaikita, Koichi; Nakayama, Naoki; Horio, Eiji; Yoshimura, Hiromi; Ono, Takamichi; Ohba, Keisuke; Tsujita, Kenichi; Kojima, Sunao; Tayama, Shinji; Hokimoto, Seiji; Matsui, Kunihiko; et al.
Abstract : Background: The aim of this study was to elucidate the correlation between angiographic coronary vasomotor responses to intracoronary acetylcholine (ACh) injection, clinical features, and long‐term prognosis in patients with vasospastic angina (VSA). Methods and Results: This is a retrospective, observational, single‐center study of 1877 consecutive patients who underwent ACh‐provocation test between January 1991 and December 2010. ACh‐provoked coronary spasm was observed in 873 of 1637 patients included in the present analysis. ACh‐positive patients were more likely to be older male smokers with dyslipidemia, to have a family history of ischemic heart disease, and to have a comorbidity of coronary epicardial stenosis than were ACh‐negative patients. ACh‐positive patients were divided into 2 groups: those with focal (total or subtotal obstruction, n=511) and those with diffuse (severe diffuse vasoconstriction, n=362) spasm patterns. Multivariable logistic regression analysis identified female sex and low comorbidity of coronary epicardial stenosis to correlate with the ACh‐provoked diffuse spasm pattern in patients with VSA. Kaplan–Meier survival curve indicated better 5‐year survival rates free from major adverse cardiovascular events in patients with diffuse spasm pattern compared with those with focal spasm pattern ( P =0.019). Multivariable Cox hazard regression analysis identified diffuse spasm pattern as a negative predictor of major adverse cardiovascular events in patients with VSA. Conclusions: ACh‐induced diffuse coronary spasm was frequently observed in female VSA patients free of severe coronary epicardial stenosis and was associated with better prognosis than focal spasm. These results suggest the need to identify the ACh‐provoked coronary spasm subtypes in patients with VSA.